Arabic-Javanese Interrogative Sentence Translation Study in The Book of Khudz 'Aqīdataka min al-Kitābi wa al-Sunnah al-Shahīhah and Al-Hudā - Sidiq, Hidayat Muhammad; Anis, Muhammad Yunus (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
Arabic-Javanese translation is a means of communication between nations as well as preservation of local languages. This research takes interrogative sentence and their translations from Arabic to Javanese. This research aims to describe the types and functions of interrogative sentences in the books of Khudz 'Aqīdataka min al-Kita>bi wa al-Sunnah al-Shahīhah (KAKSS) and Al-Huda>: Tafsir Quran Basa Jawi, as well as to describe the techniques, methods, ideology of translation. This research uses qualitative-descriptive method and Spradley's (1980) data analysis. Data collection in this study used documentary and sampling techniques then the data was validated using the theoritical triangulation method. In this research, there are three types of interrogative sentences: yes-no questions, 5W+1H questions, and rhetorical questions. The interrogative sentences in this study function as real questions, for example the creed and tawhīd in the KAKSS. Some of them function as rhetorical questions, such as denouncing and denying in the Al-Huda>. As many as 65% of the dominant techniques lean towards target language (TL). The translation methods found are semantic, free, and communicative. The translation ideology used is domestication.